EKONOMICZNA TREŚĆ INSTYTUCJI LEASINGU - Kramarek, Maciej (Wydział Prawa i Administracji UAM, 2005)
Financial lease is an alternative to a cash or hire purchase and is a more flexible way of acquiring the possession of the lease object, other than ownership. The possibility of adjusting to the current needs is of a significant practical value, but at the same time it poses a substantial difficulty in defining the constituent features of a financial lease. In order to understand its essence, two related instruments were taken as a point of reference: a lease and a rental. It was assumed that the essence of a financial lease lies in the set of features that provide for a different manner of accessing a given object, being economic functions allowing the use of the object rather that a legal form of its ownership. The results of the analysis allowed a statement that the question of the essence of a financial lease consists in considerations regarding the nature of the relations between the purchase price of the object, its market value, the amount of rent payable, and the selling price. The determination of the economically sound, or cost efficient configuration of the above parameters has become a tool used in the revision of opinions on the concept of a capital instalment as a criterion used to classify different types of lease. The differentiation between the determiners specifying the lease instalments made it possible to formulate the concluding remarks as to the essence of the financial lease.
THE ECONOMIC NATURE OF A FINANCIAL LEASE